The effect of UV-C and electrolyzed water on yeasts on fresh-cut apple at 4 degrees C - Graça, Ana (2021)
The growth of a yeast mixture, Candida sake, Hanseniaspora uvarum, Pichia fermentans, Metschnikowia pulcherrima, on fresh-cut apple (Royal gala), at 4 degrees C, was studied, as well as the reduction of yeasts using Ultraviolet-C (UV-C), acidic (AEW) and neutral (NEW) electrolyzed waters, and sodium hypochlorite (SH). Apple portions were contaminated then disinfected with UV-C (2.5-10 kJ/m(2)), AEW, NEW and SH (100 ppm). During 9 days at 4 degrees C, yeasts growth rate was 0.34 day(-1) and the stationary phase occurred after 6 days (7.42 LogCFU/g). The initial microbial reduction and the half-life time values, using the inverse hyperbola model, ranged from 1.72 to 1.81 LogCFU/g and 6.52-11.70 day (UV-C), or 0.91 to 1.96 LogCFU/g and 0.68-4.38 day (chemical treatments), where SH was the least efficient (0.92 LogCFU/g and 2.96 day). The most effective treatment was UV-C (7.5 and 10 kJ/m(2)). The yeasts psychrotrophic profile highlights the importance of avoiding contamination/cross-contaminations in all processing.